Biochemical Changes during Plantlet Regeneration in Two Accessions of Mucuna pruriens - S Raghavendra (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
The genus Mucuna is an important medicinal herb and is extensively used in traditional Indian systems of medicine for various ailments. In vitro culture technique provides an alternative to plant propagation and germplasm conservation. Our aim was to study the biochemical changes occurring during regeneration of shoots (plantlets) from explants of two accessions of Mucuna pruriens, by monitoring the efficiency of nitrogen utilization and changes in levels of some hydrolytic enzymes. A rapid micropropagation system was developed using Murashige and Skoog's (MS) medium supplemented with BAP and IAA combined. In both the accessions, 3.0mg l-1 6-BAP, in combination with 0.2mg l-1 IAA, induced shoot buds and shoot elongation; however for multiple-shoot induction, a slightly higher concentration of cytokinin, i.e., 3.5mg l-16-BAP, in combination with 0.2mg l-1 IAA, was required. Results of the present study confirm an active growth of explants revealed by nitrate assimilation enzymes and hydrolytic enzymes. It is concluded that medium composition, growth regulator combination and culture incubation conditions are all vital in both the accessions of Mucuna pruriens for induction of in vitro plant regeneration.